The Forced Active Buckling Sign: A New Clinical Test for the Diagnosis of ACL Insufficiency - Blanke, Fabian; Haenle, Maximilian; Feitenhansl, Andreas; Vogt, Stephan; Camathias, Carlo (The Journal of Knee Surgery, 2020)
Although insufficiency of the anterior cruciate ligament (ACL) is a frequent result of an injury, validated tests are associated with unsatisfying validity. Moreover, some of these tests are not easy to perform and patient's muscular resistance often limits their reliability. Therefore, with this study, we want to design an accurate test to diagnose an ACL insufficiency, which is independent of the assessor's skills and overcome any muscular resistance. Fifty patients with an isolated ACL rupture (group A; age 26.4 years ± 14.9 standard deviation [SD]; female, n = 15) and additional 50 patients with an intact ACL but meniscal lesions (group B; age 45.4 years ± 12.9 SD; female, n = 23) were consecutively included in this study. The integrity of the ACL and the menisci were evaluated by magnetic resonance imaging and verified arthroscopically. Two orthopaedic surgeons performed a pivot shift test, a Lachman's test, and our new “forced active buckling” (FAB)-sign test in all patients. The surgeons were blinded for the pathology of the knee and we randomized the tests for each patient and examiner. The sensitivity, specificity, positive predictive value, negative predictive value, and positive and negative likelihood ratios with confidence intervals were calculated and compared. With a prevalence of 0.5, the FAB-sign test revealed the best overall sensitivity of 0.78 compared with the Lachman's and pivot shift tests of 0.74 and 0.46, respectively. Also, the overall specificity of the FAB-sign test of 0.95 was higher than the Lachman's test of 0.83, however, comparable to the pivot shift test of 0.96. The FAB-sign test demonstrated the best positive and negative predictive values of 0.94 and 0.81. There was no significant difference between the two examiners concerning the accuracy of results in each test (p = 0.83). This study shows that the introduced FAB-sign test can detect an ACL insufficiency more sensitive and more specific compared to the pivot shift and Lachman's tests in the subacute phase. This is a randomized controlled diagnostic study, level 1b.
Keywords: anterior cruciate ligament; ACL insufficiency; test; examination